Facile synthesis and self-cleaning application of bimetallic (CuSn, CuNi) dendrites - Biswas, Anupam; Kulkarni, Mayuresh A.; Bakthavatsalam, Rangarajan; Mondal, Sourik K.; Dwivedi, Pravin K.; Shelke, Manjusha V.; Devi, Radhamonyamma N.; Banpurkar, Arun G.; Kundu, Janardan (Chemistryselect, 2017)
Bimetallic dendrites (Au, Ag, Pt, Pd) have received intense research interest due to their applications in catalysis and sensing. However, reports on rational synthesis of non-noble bimetallic dendrites that finds self-cleaning applications are scanty. Here, we demonstrate one step co-reduction based galvanic replacement reaction (GRR) for synthesis of alloyed bimetallic dendrites (CuSn, CuNi) with controlled surface roughness and chemical composition. Probing their growth process reveals that i) for CuSn dendrites, co-reduction of Cu2+ and Sn2+ is observed throughout GRR; ii) for CuNi dendrites, Cu nanoparticle, that deposits initially, augments the reduction of Ni2+ which leads to CuNi alloy phase formation during later stages of GRR. These dendrites, naturally having dual degree of surface roughness (micro/nano), have been exploited here for fabricating superhydrophobic surfaces (SHS) with excellent self-cleaning abilities. They show enabling properties such as high contact angle, minimal contact angle hysteresis, and excellent Cassie state stability with no impalement. They maintain superhydrophobicity when exposed to different environmental conditions (low temperature, high temperature, exposure to corroding solutions and UV radiation). The present facile methodology for fabrication of bimetallic dendrites is beneficial for low-cost production of functional nano/micro-materials.